Enabling Environments for Civic Engagement in PRSP Countries - World Bank (Washington, DC, 2012)
It is now increasingly recognized that, alongside the state and the market, civil society is a critical factor in determining the level, pace and equity of a country's economic, social and political development. Civic engagement is the participation of private actors in the public sphere, conducted through direct and indirect interactions of civil society organizations and citizens-at-large with government, multilateral institutions and business establishments to influence decision making or pursue common goals. It is a process that organizes citizens or their entrusted representatives to "influence, shape and control public affairs and development initiatives, implementation and resources. Under the right conditions civic engagement can promote development and improve the economic and social conditions of the poor. How civil society can maximize its potential in alleviating poverty and promoting social accountability, and what types of laws, regulations, governance and cultural norms are needed to create the most conducive environment in which civil society operates, is less well understood.